(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
At the origins of men’s work was katabasis, a man’s descent when struck by love, grief and the mourning of an absent father. Recently, the work veered towards defensive notions of masculinity, a reaction to the emergence of woke capitalism, the politics of injury and the poisoned solidarities between sections of feminism and the evangelical and political Right.